PERTANGGUNGJAWABAN HUKUM MUCIKARI DALAM EKSPLOITASI SEKSUAL ANAK : ANALISIS KASUS PROSTITUSI ANAK MELALUI APLIKASI MICHAT - Mutia Ayu Wulandari; Sekaring Ayumeida Kusnadi (Fakultas Ilmu Sosial dan Humaniora, 2025)
This study investigates pimps' legal liability in cases involving child sexual exploitation using the Michat application, which has gained popularity recently. The main topic of the study is Indonesia's laws pertaining to child sex exploitation, how those laws determine pimps' legal responsibility for their actions, and how harsher punishments are applied to discourage offenders. According to the case study, pimps may face charges under several statutes, such as the Child Protection Law, the Information and Electronic Transactions Law (ITE), and the Criminal Code (KUHP). In addition to human trafficking, pimps are also accountable for morally repugnant offenses involving children. Law enforcement against pimps is crucial to prevent further exploitation and to serve as a deterrent. It is concluded that legal accountability for pimps in this case is highly significant and requires stricter law enforcement to protect children from sexual exploitation, as well as to strengthen existing regulations in combating this criminal practice.